Mutu Organoleptik dan Daya Terima Konsumen Pada Sagu Lempeng Abon Ikan Tuna: Mutu Organoleptik dan Daya Terima Konsumen Pada Sagu Lempeng Abon Ikan Tuna - wahab, iswandi wahab (Jurnal Kelautan, Lingkungan, dan Perikanan, 2025)
Tuna sago floss is a processed product from tuan fish floss and cassava flour. Tuna is processed into kenjudian fish floss as an additional ingredient in the processing of sago lempeng products which are then mixed with chicken broth and pepper as a flavor enhancer in sago floss products. Making sago floss in research that is appropriate in processing sago floss. Making sago floss in this study consists of 5 different treatments, to determine the appropriate dosage in processing tuna sago floss. This research will be conducted at the Sago Lempeng Production House, Dehegila Village, South Morotai District, in July 2024. The purpose of this study was to analyze the organoleptic quality of sago plates with the addition of tuna fish floss and to analyze the level of panelists' preference for sago plates with the addition of tuna fish floss. The data analysis method used descriptive analysis and was displayed through tables and graphs and was also documented with pictures. The results of the study of the addition of tuna fish floss in the manufacture of sago plates in the A0_A4 treatment can be concluded that, based on organoleptic analysis, the provision of tuna fish floss in the manufacture of sago plates does not affect the appearance, color, and texture of sago plates. While the average hedonic test of panelists gave a liking assessment to all sago formulas for all indicators. Keywords: Organoleptic, Hedonic Test, Tuna fish floss, cassava, sago, Tuna fish floss.